Effect of ductus deferens lavage on the time to achieve azoospermia in patients undergoing vasectomy - Francisco Barros de Oliveira; Vadelias Xavier Pereira; Fernando Rocha Oliveira; Luiz Carlos de Abreu; Blanca Elena Guerrero Daboin; Alex Rey Norberto; Luiz Vinicius de Alcantara Sousa; Luis Fernando B. Tavares; Sidney Glina (Clinics, 2018)
OBJECTIVE: To evaluate the effect of normal saline lavage of the distal vas deferens ampulla in patients undergoing vasectomy on the time to achieve azoospermia. METHODS: A prospective randomized study of 60 men divided into two groups, group lavage (GL, n=30) in which distal vas deferens ampulla lavage was performed with 10 ml of normal saline during the vasectomy, and group without lavage (GWL, n=30) in which control patients received only a vasectomy. The patients provided sperm for semen analysis at the 5th, 10th, 15th, 20th and 25th ejaculations. RESULTS: Fifteen participants in GL and 16 in GWL, for a total of 31 patients, were excluded due to not completing the control spermiogram. The tests carried out at the five ejaculations showed immobile spermatozoa in 40 and 85.71%, 66.67 and 78.57%, 93.33 and 85.71%, 86.67 and 71.43%, and 93.33 and 85.71% of participants in GL and GWL, respectively. CONCLUSION: Vas deferens duct lavage with 10 ml of normal saline during vasectomy did not decrease the time required to achieve postoperative azoospermia.